Transfer and engineering of immune receptors to improve recognition capacities in crops - Rodríguez-Moreno, Luis Gabriel; Song, Yin; Thomma, Bart (Elsevier Ltd, 2017)
Immune receptors are pivotal elements of the plant immune system that act as sentinels for microbial invasion. Knowingly or unknowingly, breeding for resistance has largely relied on the transfer of immune receptor recognition specificities between plant genotypes. For decades such transfers were limited to crossable species. However, advents in transgene technologies have allowed overcoming species barriers. Novel strategies for mining of recognition specificities, combined with our recently increased understanding of immune receptor functioning, allows to increase and alter recognition specificities, which should ultimately increase the spectrum of recognition specificities that are available to control plant diseases in crops.
En este caso, la versión posprint (aceptada) coincide con la versión publicada que es el pdf del editor y adjunto.
Keywords: Plantas - Resistencia a enfermedades y plagas; Plant immune receptors